Rotary ultrasonic machining of carbon fiber reinforced plastic composites: using cutting fluid versus cold air as coolant - Cong, W. L.; Feng, Q.; Pei, Zhijian J.; Deines, Timothy W.; Treadwell, C. (My University, 2011)
Drilling is involved in many applications of carbon fiber reinforced plastic (CFRP) composites. Rotary ultrasonic machining (RUM) has been successfully employed to drill holes in CFRP using either cutting fluid or cold air as coolant. However, there are no reported studies to compare the results in RUM of CFRP using these two types of coolant. This paper, for the first time, presents an experimental study to compare cutting force, torque, surface roughness, burning of machined surface, and tool wear in RUM of CFRP using these two types of coolant. This study will result in knowledge about machining conditions under which it is feasible to use cold air instead of cutting fluid and differences in machined hole quality produced using cold air versus cutting fluid.
Keywords: Carbon fiber reinforced plastic composite; Cold air; Coolant; Cutting fluid; Drilling; Rotary ultrasonic machining